Comparison of Cost‐Effectiveness of Vitamin D Screening with That of Universal Supplementation in Preventing Falls in Community‐Dwelling Older Adults. Issue 5 (30th April 2013) - Lee, Richard H.; Weber, Thomas; Colón‐Emeric, Cathleen
<x xml:space="preserve">Abstract</x> Objectives To compare the cost‐effectiveness of population screening for vitamin D insufficiency with that of universal vitamin D supplementation in community‐dwelling older adults. Design A Markov decision model simulating follow‐up over a 36‐month period. Published data were used to estimate values for the model, including costs (measured in 2011 U.S. dollars), utilities (measured in quality‐adjusted life years (QALYs)), and probabilities. Setting Decision analysis simulation from a societal perspective. Participants Hypothetical cohort of community‐dwelling women and men aged 65 to 80. Measurements Net monetary benefit (NMB) was calculated by subtracting the incremental cost of the strategy from the product of incremental QALYs and willingness‐to‐pay threshold. A higher NMB indicates greater cost‐effectiveness. Results In women aged 65 to 80, population screening was slightly more cost‐effective than universal supplementation, with an incremental NMB of $224 compared with $189 (P < .001). Population screening in men was also more cost‐effective than universal supplementation (incremental NMB $298 vs $260, P < .001). Results differed according to age group. In those aged 65, population screening had cost‐effectiveness similar to that of universal supplementation in women ($59 vs $71) and men ($114 vs $120), whereas in those aged 80, population screening was substantially more cost‐effective than universal supplementation in women ($563 vs $428) and men ($703 vs $571). Conclusion Population screening and universal supplementation for vitamin D insufficiency are cost‐effective strategies in community‐dwelling older women and men. In the oldest old, population screening may be more cost‐effective than universal supplementation.